The strategic partner roles through employee relations and communication to improve performance in the perspective of Malaysian SMES / Ivana Chandra Voo, Janice Ong May Li, Pang Yeng Yuan and Sharon@Rebecca Tan - Voo, Ivana Chandra; Janice, Ong May Li; Pang, Yeng Yuan; Tan, Sharon@Rebecca (UiTM Cawangan Johor, 2023)
The issue of fitting human resource management practices to business strategy has become increasingly relevant over the few years and small and medium enterprises (SNfEs) are no exception. Strategic human resource management (SHRM) has now come to be recognised as an in separable part of a firm 's competitive advantage. On the other hand, employee relations and communications are considered important human resource management (HRM) practices to ensure effective knowledge and information transfer from one person to another. Therefore, in the present study, we have made efforts to study the relationship between employee relations and communications and SNfEs performance through the mediation roles of strategic partners. The conceptual framework for the present study adopted Ulrich's business partner role model as a mediator. Findings from the study conclude that employee relations and communications support performance when aligned with the roles of strategic partners. Based on the findings, this paper has valuable implications for both theory and in practice as it offers contributions both to SNfEs and academics on the importance of effective employee relations and communication practices. Keywords: SHRU strategic partner, SMEs, HRM practices